2000
DOI: 10.7557/2.20.2-3.1505
|View full text |Cite
|
Sign up to set email alerts
|

Viral diseases of northern ungulates

Abstract: This paper describes viral diseases reported in northern ungulates and those that are a potential threat to these species. The following diseases are discussed: bovine viral diarrhoea/mucosal disease (BVD/MD), alphaherpesvirus infections, malignant catarrhal fever (MCF), poxvirus infections, parainfluenza type 3 virus infection, Alvsborg disease, foot-and-mouth disease, epizootic haemorrhage disease of deer and bluetongue disease, rabies, respiratory syncytial virus infection, adenovirus infection, hog-cholera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…These are two reindeer populations with very limited contact with cattle, which also supports this view. Also other wild cervid populations in Norway and other European countries are hosting alpha-herpesviruses and pestiviruses (Thiry et al, 1988;Frölich & Hoffman, 1995;Anonymous, 1999;Frölich, 2000;Lillehaug et al, 2003). Pestivirus isolates from a zoo-reindeer, a giraffe and a bison are tentative new species of the genus (Avalos-Ramirez et al, 2001;Becher et al, 2003), and recent characterisation of pestivirus isolates from roe deer from Germany (Fischer et al, 1998), Pyrenean chamois (Rupicapra pyrenaica pyrenaica) (Arnal et al, 2004), and pronghorne antelope (Antilocopra americana) from USA (Vilcek et al, 2005) indicates that these viruses do not fit with the pestivirus species identified so far, and that several distinct pestiviruses might exist among wildlife species.…”
Section: Discussionmentioning
confidence: 99%
“…These are two reindeer populations with very limited contact with cattle, which also supports this view. Also other wild cervid populations in Norway and other European countries are hosting alpha-herpesviruses and pestiviruses (Thiry et al, 1988;Frölich & Hoffman, 1995;Anonymous, 1999;Frölich, 2000;Lillehaug et al, 2003). Pestivirus isolates from a zoo-reindeer, a giraffe and a bison are tentative new species of the genus (Avalos-Ramirez et al, 2001;Becher et al, 2003), and recent characterisation of pestivirus isolates from roe deer from Germany (Fischer et al, 1998), Pyrenean chamois (Rupicapra pyrenaica pyrenaica) (Arnal et al, 2004), and pronghorne antelope (Antilocopra americana) from USA (Vilcek et al, 2005) indicates that these viruses do not fit with the pestivirus species identified so far, and that several distinct pestiviruses might exist among wildlife species.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine-viral-diarrhea virus type 1 causes enteritis, mucosal disease, infections, and respiratory and reproductive disorders in cattle (Baker 1995), but this apparently is not the case in elk (Tessaro et al 1999). The epidemiology of these viruses in wild elk remains unresolved, and continued research is needed (Depner et al 1991, Aguirre et al 1995, Frolich 2000.…”
Section: Blood Characteristics and Disease Seroprevalencementioning
confidence: 99%
“…Although most PI-3 infections in ungulates are mild or clinically undetectable and no severe clinical effects have been demonstrated in elk, death can result when secondary infections of Pasteurella spp. cause pneumonia (Martin 1996, Frolich 2000, Storz et al 2000. Bovine-viral-diarrhea virus type 1 causes enteritis, mucosal disease, infections, and respiratory and reproductive disorders in cattle (Baker 1995), but this apparently is not the case in elk (Tessaro et al 1999).…”
Section: Blood Characteristics and Disease Seroprevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Neospora caninum, Toxoplasma gondii, Dicrocoelium lanceolatum, Fascioloides magna, Echinococcus granulosus), or vector-borne transmission (Bluetongue virus, Epizootic Hemorrhagic Disease virus, Anaplasma marginale, Babesia sp.) (Smits, 1991;Aguirre et al, 1995;Frölich, 2000;Corn and Nettles, 2001;Conner et al, 2008;Corn et al, 2010;Miller et al, 2013). The response of elk to cattle presence and to pasture management practices likely affects inter-species interactions, and the risk of transmission of various types of pathogens between cattle and elk.…”
Section: Introductionmentioning
confidence: 96%